THE EFFECT OF BRAND IMAGE AND MIX MARKETING ON CUSTOMER LOYALITY IN PT. SUNGAI BUDI GROUP BENGKULU - Riska Melda Sari; Sulisti Afriani; Tito Irwanto (Perkumpulan Dosen Muda (PDM) Bengkulu, 2020)
Target of this research is to know Influence of Brand Image to Customer Loyality at PT. Sungai Budi Group Bengkulu (Case Study Customer Of Cooking Oil of Rose Brand) and to know Influence of Marketing Mix to Customer Loyality at PT. Sungai Budi Group Bengkulu (Case Study Customer of Cooking Oil of Rose Brand) and also To know Influence of Brand Image and of Marketing Mix by together to Customer Loyality at PT. Sungai Budi Group Bengkulu (Case Study Customer of Cooking Oil of Rose Brand). Method Analysis the used is Test validity, Test Reliabilitas, Simple Linear Regression, Coefficient of Determination, Test F and Test of t.